Advances in librarianship. Vol. 16 - Godden, Irene P., 1932- (Emerald, 1992)
A reference source for developments in the field of libraries and library science. Areas of public, college, university, primary and secondary schools and special libraries are given critical analysis by professionals in the field of librarianship, in teaching and in research. The text is intended for use by professional librarians and information scientists and includes chapters on document delivery, co-operative cataloguing and strategic quality management in libraries.
Includes index.
Keywords: Library science.; Information science.; elektronické knihy; electronic books